Multi-sensory spa design a case study of a day spa in Quezon City - Mitra, Joanne Grace S.
This case study sought to examine the design of a selected Day Spa to determine whether it satisfied the provisions of multi-sensory design. A combination of descriptive and evaluative research was utilized, using observation and survey to gather data. The instruments used in the study include survey questionnaires, a journal and a digital camera. The selected Day Spa which is found in Quezon City had a maximum capacity of 25 clients at one time. Simple random sampling was used to select the 22 respondents of the survey consisting of 4 male and 18 female clients. The qualitative information obtained through observation was analyzed by tabulating them according to the dimensions of multi-sensory design while results of the survey questionnaires were presented in graphs. Results show that the interior of the selected Day Spa manifested the visual, tactile, olfactory, and aural dimensions of multi-sensory design in different degrees. The visual dimension had the greatest impact on the users despite its limitations. This may be attributed to the sense of sight, which prevail over most sensory experiences being the most developed sense. Th tactile dimension was the least effective of all the dimensions because of the spa's furniture pieces and room temperature that were problematic. This visual dimension obtained the highest ranking with respect to its impact on the users, followed by olfactory, aural, and tactile dimensions. Overall, the spa was not successful in creating a relaxing and healing environment through the design of its interior because two out of the four dimensions of multi-sensory design, visual and tactile, were generally unsuccessful in obtaining positive responses from the respondents. To attain a total healing environment, all dimensions of a multi-sensory experience must be evident and expressed well in design.